METHODS OF GOODWILL ASSESSMENT AND WAYS TO IMPROVE THEM (American Journal of Business Management, Economics and Banking, 2025)
For many companies, goodwill is the most significant asset, for which such concepts as identifiability and isolation are not typical. Goodwill simplifies asset manipulation, but at the same time, neither many accountants nor the management of these companies know how to accurately and correctly evaluate goodwill, since its real value is formed when the organization is sold. But goodwill evaluation is necessary, and goodwill can be evaluated in various ways. The article considers the main methods of goodwill evaluation, suggests ways to improve them and develops its own method for evaluating goodwill.